2012
DOI: 10.1002/glia.22348
|View full text |Cite
|
Sign up to set email alerts
|

A distinct set of synaptic‐like microvesicles in atroglial cells contain VGLUT3

Abstract: There is increasing evidence for vesicular release of glutamate from astrocytes. We have previously demonstrated existence of VGLUT1 on astrocytic synaptic-like microvesicles (SMLVs) in several brain regions indicating a role in astroglial glutamate release. As VGLUT3 is prominently expressed in non-neuronal cells, this prompted us to investigate whether VGLUT3 is also involved in astroglial release of glutamate. Confocal microscopic investigations revealed that astrocytes in the hippocampus and the frontal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 79 publications
2
30
1
Order By: Relevance
“…This does not contradict the presence of VGLUTs in astrocytes, as they have all been found to be localized in acutely isolated astrocytes both at the protein level (236,268,458) and the mRNA level (458). In line with this are immunohistochemical results, showing that VGLUT1, VGLUT2, and VGLUT3 are indeed located within delicate perisynaptic astrocytic processes in the intact brain (33,37,123,295,296,333,458). Interestingly, VGLUT3 has been shown to be upregulated in astrocytes after focal cerebral ischemia (360).…”
Section: Vesicular Transportersmentioning
confidence: 52%
See 1 more Smart Citation
“…This does not contradict the presence of VGLUTs in astrocytes, as they have all been found to be localized in acutely isolated astrocytes both at the protein level (236,268,458) and the mRNA level (458). In line with this are immunohistochemical results, showing that VGLUT1, VGLUT2, and VGLUT3 are indeed located within delicate perisynaptic astrocytic processes in the intact brain (33,37,123,295,296,333,458). Interestingly, VGLUT3 has been shown to be upregulated in astrocytes after focal cerebral ischemia (360).…”
Section: Vesicular Transportersmentioning
confidence: 52%
“…Using knockout controls for VGLUT1-3 antibodies, one confocal study concludes that none of the VGLUTs is present in astrocytes (222). In our previous studies (295,296), the VGLUT labeling in astrocytes was also controlled for by using VGLUT1 and VGLUT3 knockout tissue. The reasons for discrepancies between the results of the former and the latter studies are obscure.…”
Section: Vesicular Transportersmentioning
confidence: 93%
“…Although these alternative explanations remain possible, exogenous application of the glutamate receptor agonist AMPA was capable of rescuing the duration of oscillations that were reduced with defective vesicle fusion in our model. Coupled with recent evidence that perisynaptic astrocytes express the vesicular glutamate transporters VGLUT1 and VGLUT3 (49,50) and that glutamate accumulates in synaptic-like microvesicles in the perisynaptic processes of astrocytes at a concentration comparable to that in synaptic vesicles of excitatory nerve terminals (51), glutamate may be said to in some way mediate the impact of astrocytes on network dynamics. The fact that the expression of tetanus toxin did not cause evident changes in basal synaptic transmission, as measured in cultured and in acute slices, strongly suggested that the TeNT gene, delivered by lentiviral vectors in slice cultures or integrated into the genome of transgenic mice, was exclusively expressed in astrocytes and not in neurons.…”
Section: Discussionmentioning
confidence: 86%
“…In rat hippocampus, VGLUT3 is found in astrocytes and postulated to be crucial for Ca 2+ -dependent astroglial glutamate exocytosis [21]. Moreover, intracellular Ca 2+ -release and Ca 2+ -oscillations were observed in sclerotic hippocampal astrocytes, along with upregulation of the synaptic vesicle protein SNAP23.…”
Section: Discussionmentioning
confidence: 95%